2020
DOI: 10.1177/0959683620902214
|View full text |Cite
|
Sign up to set email alerts
|

Late Glacial and Holocene records of tree-killing conifer bark beetles in Europe and North America: Implications for forest disturbance dynamics

Abstract: Outbreaks of conifer bark beetles in Europe and North America have increased in scale and severity in recent decades. In this study, we identify existing fossil records containing bark beetle remains from the end of the Last Glacial Maximum (~14,000 cal. yr BP) to present day using the online databases Neotoma and BugsCEP and literature searches, and compare these data with modern distribution data of selected tree-killing species. Modern-day observational data from the Global Biodiversity Information Facility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 83 publications
0
4
0
Order By: Relevance
“…Although not investigated on a large scale, fire likelihood and severity can be increased by insect outbreaks (Rogers et al, 2020) because changing fuel conditions through, for example, defoliation negatively affects timber and fiber production or changes the tree water budget (Schafstall et al, 2020). Beetle-induced changes to foliar moisture have the greatest effects on flammability (Fettig et al, 2021).…”
Section: Fire Drivers Within the Last Ca 1750 Years In The Suwałki Re...mentioning
confidence: 99%
“…Although not investigated on a large scale, fire likelihood and severity can be increased by insect outbreaks (Rogers et al, 2020) because changing fuel conditions through, for example, defoliation negatively affects timber and fiber production or changes the tree water budget (Schafstall et al, 2020). Beetle-induced changes to foliar moisture have the greatest effects on flammability (Fettig et al, 2021).…”
Section: Fire Drivers Within the Last Ca 1750 Years In The Suwałki Re...mentioning
confidence: 99%
“…For example, Schafstall et al (2022) found only three main bark beetle outbreaks between 1400 BP and the present in the High Tatras (Slovakia) (the last one post-2004 after the disas-trous windstorm Elizabeth of 19 November 2004), in which Ips typographus was rather low in numbers. Moreover, bark beetles remain rather neglected in palaeoecology with only a few dozen reported sites in Europe for the whole of the Holocene (Schafstall et al, 2020).…”
Section: The Database and Data Uncertaintymentioning
confidence: 99%
“…However, pests and pathogens are difficult to detect using traditional palaeoecological approaches, such that even in ecosystems with regular insect outbreaks (e.g. bark beetles), the outbreaks can only be detected through indirect means (Morris & Brunelle, 2012) or at small forest hollow sites (Schafstall et al., 2020). Hence, whether pests and pathogens had any effect on American beech dynamics during the Holocene remains possible but unknown and unstudied.…”
Section: Discussionmentioning
confidence: 99%